Cardiac Hemodynamics, Tissue Oxygenation, and Functional Capacity in Post-COVID-19 Patients - Nascimento, Elizane Poquiviqui do; Nascimento, Larissa Fernanda Estevam do; Castro, Lhara de Freitas; Barros, Vilena Cavalcante de; Bandeira, Emily Rachel Pereira; Wanderley e Lima, Thiago Bezerra; Otto-Yáñez, Matías; Fregonezi, Guilherme Augusto de Freitas; Resqueti, Vanessa Regiane (Medicina (Kaunas, Lithuania), 2025)
Background and Objectives: This study aimed to evaluate and compare the functional capacity of post-COVID-19 patients with a control group and analyze cardiac hemodynamics and muscle tissue oxygenation responses during assessment protocols in both groups. Materials and Methods: A cross-sectional study was conducted involving patients with COVID-19 and a control group who were all aged ≥18 years. Participants underwent two functional capacity tests: the one-minute sit–stand test (1-STS) and the six-minute walk test (6MWT). Cardiac hemodynamic responses were evaluated using impedance during the 1-STS, and tissue perfusion responses in the oxygenation were recorded during and after both tests. The Friedman test was used for within-group and the Mann–Whitney test was used for between-group comparisons. Results: Thirty-six post-COVID-19 patients (median age 36 years, BMI 26.51 kg/m2) and eleven control subjects (median age 25 years, BMI 23.71 kg/m2) were enrolled. The post-COVID-19 group showed a 20% decrease in 6MWT distance (p = 0.0001) and a 28% decrease in 1-STS repetitions (p = 0.01) versus the control group. Cardiac hemodynamic differences were observed in the post-COVID-19 group during the 1-STS, with reductions in the stroke volume index (18%, p = 0.004), cardiac index (21%, p = 0.0009), Contractility Index (78%, p = 0.0001), and Ejection Fraction (29%, p = 0.0003) and increases in Systemic Vascular Resistance (25%, p = 0.03) and the Systemic Vascular Resistance Index (27%, p = 0.0007). Tissue oxygenation during the 6MWT and 1-STS showed no significant differences between groups. Conclusions: The post-COVID-19 subjects exhibited a reduction in functional capacity, changes in hemodynamic responses related to cardiac and systemic vascular resistance, and a similar pattern of muscle oxygen delivery and consumption in both tests